Consumer preferences for country of origin of foreign fruit: does consumer animosity matter? - Vu Hung Dang; Thang Vinh Doan (Cogent Business & Management, 2024)
Previous research suggests the existence of variables that can moderate the influence of country of origin (COO) on consumer preferences for food products. However, there is a scarcity of studies investigating the moderating effect of consumer animosity on the connection between COO attributes and consumer preferences. This study represented an initial attempt to examine consumer preferences for imported fruit from countries involved in disputes with a target country, compared to countries with fewer or no disputes. A choice-based experiment was conducted with 180 respondents in Vietnam's Mekong River Delta region, using Random Utility Theory (RUT) and the Generalized Multinomial Logit model. The results show significant heterogeneity in consumer preferences for attributes such as COO, traceability label, organic label, and price. However, there is homogeneity in preference for fruit size. Consumer animosity towards a specific country plays a crucial role in shaping choice behavior, as higher animosity leads consumers to prefer the same product from other countries. This study effectively addresses domestic bias by isolating the effects of consumer ethnocentrism, making it a valuable contribution to the field. It also provides practical implications for fruit importers, domestic producers, and retailers in Vietnam by highlighting the importance of different attributes of foreign fruit.
Keywords: 650; consumer animosity; consumer preference; country of origin; foreign fruit; GMNL model